2008
DOI: 10.1063/1.2938081
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional atom probe analysis of green- and blue-emitting InxGa1−xN∕GaN multiple quantum well structures

Abstract: The three-dimensional atom probe has been used to characterize green- and blue-emitting InxGa1−xN∕GaN multiple quantum well structures with subnanometer resolution over a 100nm field of view. The distribution of indium in InxGa1−xN samples with different compositions is analyzed. No evidence is found wherein the indium distribution deviates from that of a random alloy, which appears to preclude indium clustering as the cause of the reported carrier localization in these structures. The upper interface of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 18 publications
6
68
1
Order By: Relevance
“…Our results reveal that the experimentally estimated localization length is consistent with the hole wave function localization, since the localization length of the electrons will be mainly determined by the size of in-plane WWFs, at least for the here considered 25% InN system. It should also be noted that we have studied here the lower limit (5 nm) of the experimentally reported values (5-10 nm) [49]. Thus one could expect that when increasing the in-plane dimension of the WWFs, the localization length of the electrons is of the order 5-10 nm.…”
Section: Comparison With Experimental Datamentioning
confidence: 93%
See 2 more Smart Citations
“…Our results reveal that the experimentally estimated localization length is consistent with the hole wave function localization, since the localization length of the electrons will be mainly determined by the size of in-plane WWFs, at least for the here considered 25% InN system. It should also be noted that we have studied here the lower limit (5 nm) of the experimentally reported values (5-10 nm) [49]. Thus one could expect that when increasing the in-plane dimension of the WWFs, the localization length of the electrons is of the order 5-10 nm.…”
Section: Comparison With Experimental Datamentioning
confidence: 93%
“…To realize different microscopic configurations, our calculations have been repeated ten times with changing the atomic distribution. Furthermore, experimental studies reveal WWFs at the upper QW interface [49,52]. The diameter of these well-width fluctuations is ≈5-10 nm, while their height is between one and two monolayers.…”
Section: Model Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of localisation mechanisms has been proposed including indium clusters, 20,[43][44][45][46] QW width fluctuations, 38,47 and random fluctuations in the local In fraction. 48,49 Of these possibilities, the case for In clusters was largely disproved in the work of Smeeton et al 50 and Galtrey et al, 51 who showed that the evidence for In clustering could be attributed to electron beam damage in the TEM measurements.…”
Section: Polar Quantum Wellsmentioning
confidence: 97%
“…As analyzed before, 9 the bright regions are on the order of micrometers in size, and have smaller bandgap energy than the dark regions, due to local higher indium concentration 10 or larger quantum well thickness. 11 So carriers are localized in small bandgap energy bright regions.…”
Section: Ecs Journal Of Solid State Science and Technology 4 (2) R10mentioning
confidence: 99%